The in vitro Activity of Omadacycline Alone and in Combination Against Carbapenem-Resistant Klebsiella pneumoniae - Du Y; Liu Y; Liu T; Pan F; Mu S; Zhu Y; Gao H; Jing X; Wang X; Liu Y; Wang S (Infection and Drug Resistance)
Yingying Du,1– 3,* Yan Liu,4,* Tong Liu,1 Fen Pan,5 Shikui Mu,2 Yunlou Zhu,2 Hanlu Gao,2 Xin Jing,2 Xing Wang,6 Yuhao Liu,2 Sheng Wang1– 3 1Intensive Care Medical Center, Tongji Hospital, School of Medicine, Tongji University, Shanghai, 200065, People’s Republic of China; 2Department of Critical Care Medicine, Shanghai Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of China; 3Key Laboratory of Pathogen-Host Interaction, Ministry of Education, Shanghai, 200092, People’s Republic of China; 4Department of Clinical Microbiology, Shanghai Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of China; 5Department of Laboratory Medicine, Children’s Hospital of Fudan University, National Children’s Medical Center, Shanghai, 200032, People’s Republic of China; 6Department of Laboratory Medicine, Shanghai Children’s Medical Center, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuhao Liu; Sheng Wang, Email lyh-7906@163.com; wangsheng@tongji.edu.cnObjective: This study aimed to evaluate the in vitro activity of omadacycline (OMC) and OMC-based combination therapy against carbapenem-resistant Klebsiella pneumoniae (CRKP).Methods: The broth microdilution assay assessed the in vitro susceptibility of CRKP to OMC. The checkerboard assay was performed to evaluate the activity of OMC combined with polymyxin B (PB), amikacin (AN), or meropenem (MEM) against KPC-producing (class A) CRKP strains, and OMC combined with PB, aztreonam (ATM), MEM, or AN against class B and class A plus class B CRKP strains. Synergistic effects of OMC and PB were further evaluated by time-kill assays in the KPC-producing CRKP strains.Results: Broth microdilution assays revealed a notable variation in susceptibility between KPC-producing and class B CRKP strains, with MIC50/90 of 32/32 mg/L and 0.5/8 mg/L, respectively. Although KPC-producing CRKP strains were resistant to OMC, a synergistic effect was observed in 37.5% of KPC-producing CRKP strains when OMC was combined with PB. In the nine KPC-producing CRKP strains, time-kill assays found that cell densities of six strains (66.7%) decreased by 3.61 ± 0.23 log10 CFU/mL compared to the initial inoculum after 2 hours of PB exposure. The cell densities further decreased by an average of 2.38 ± 0.23 log10 CFU/mL when the six strains were exposed to OMC plus PB, confirming their potent synergism.Conclusion: OMC monotherapy is ineffective against KPC-producing CRKP strains, but OMC plus PB has a potent synergistic effect on them, suggesting that OMC plus PB is the preferred combination therapy against KPC-producing CRKP in vitro.Keywords: Klebsiella pneumoniae, carbapenem resistance, omadacycline, polymyxin B, antibiotic combination treatment, time-kill test